x(t) = -u(t-3)+2u​(t+1)-2u(t​-1)+u(t-3)

31 views (last 30 days)
cadburry oreo
cadburry oreo on 4 Oct 2020
Answered: Jonas on 8 Feb 2023
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new

Answers (1)

Jonas
Jonas on 8 Feb 2023
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')

Categories

Find more on Systems of Nonlinear Equations in Help Center and File Exchange

Tags

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!